Dinamika dakwah Islam di era modern - Pimay, Awaludin; Savitri, Fania Mutiara (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2021)
The development of science and technology has had an impact on the ethical joints of Muslims in this modern era. To anticipate the complexities of modern society, the da'i must prepare da'wah strategies and materials that are more directed at anticipating the tendency of society. Modernization in the midst of onslaught and globalization that takes place very quickly and it is difficult to predict the direction of the da'i must be carried out continuously effectively. This study aims to review effective da'wah strategies in the midst of changing da'wah dynamics. The research method used is descriptive qualitative research with the data collection technique is literature study. The literature study method is an activity related to the method of collecting library data, reading and taking notes and managing research materials. The results of the study indicate that da'wah can play an active role in the modern era if the da'i as a preacher is can participate development of the times so that da'wah as an illuminator is able to give a role to a society that deifies science and technology. In addition, da'i in modern life, da'wah must be directed to mad'u with the